Copper toxic stress on Aloe barbadensis and its antioxidant response - Ong, Ghim Hock; Aya Omer, Mustafa Omer; Subramaniam, Geetha (2015)
Toxic levels of copper (Cu) can cause deleterious effects such as protein denaturation and oxidative stress. Plants could respond to heavy metal tolerance through various mechanisms including alteration of their enzymatic antioxidant activity which acts as a toxicity tolerance mechanism. The aim of this study was to investigate the relationship between Aloe barbadensis enzymatic antioxidants and its response to different concentrations of Cu (control, 1ppm, 3ppm and 5ppm). A. barbadensis were treated with different concentrations of Cu on a 4 days cycle for a period of 21 days. Activity of the antioxidant enzymes namely superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and guaiacol peroxidase (GPX) were determined after 21 days. SOD exhibited changes in activity in response to increased Cu concentration and showed significantly higher (P<0.05) at 3ppm and 5ppm Cu compared to 1ppm. CAT exhibited changes in activity as Cu concentration increased and showed no significant difference among the three levels of Cu. APX exhibited changes in activity as Cu concentration increased and showed significantly higher (P<0.05) at 1ppm when compared to 3ppm and 5ppm. GPX exhibited changes in activity as Cu concentration increased and showed no significance within three levels of Cu. In conclusion, the enzymatic antioxidant exhibited relationship in activity. SOD antioxidant was found to be the most effective in scavenging the reactive oxygen species as it increases during copper stress and shows consistency in activity.